Poor association between dihydropyrimidine dehydrogenase (DPYD) genotype and fluoropyrimidine‐induced toxicity in an Asian population. (16th December 2022) - Kanai, Masashi; Kawaguchi, Takahisa; Kotaka, Masahito; Manaka, Dai; Hasegawa, Junichi; Takagane, Akinori; Munemoto, Yoshinori; Kato, Takeshi; Eto, Tetsuya; Touyama, Tetsuo; Matsui, Takanori; Shinozaki, Katsunori; et al.
Abstract: Objective: Dihydropyrimidine dehydrogenase ( DPYD ) genotype is closely associated with fluoropyrimidine (FP)‐induced toxicities in Caucasian population and European Medicines Agency now recommends DPYD genotype‐based FP dosing strategy. Patients and Methods: The current study aimed to investigate their impact on FP‐related toxicities in an Asian population using genome‐wide association study (GWAS) data set from 1364 patients with colon cancer. Results: Among 82 variants registered in the Clinical Pharmacogenetics Implementation Consortium, 74 DPYD variants were directly genotyped in GWAS cohort; however, only 7 nonsynonymous DPYD variants (CPIC variants) were identified and none of the four recurrent DPYD variants ( DPYD *2A, c.2846A>T, c.1679T>G, c.1236G>A) were included. Seven CPIC variants were investigated for their association with the incidence of FP‐related toxicities; however, none of these variants revealed a significant correlation with FP‐related toxicities. Conclusion: These data suggested that the DPYD genotype registered in CPIC plays a minor role in FP‐related toxicities in an Asian population. Abstract : DPYD genotype‐based fluoropyrimidine dosing strategy is recommended in a Caucasian population, In contrast, considering the low prevalence of impaired DPYD variants in an Asian population, universal DPYD screening does not appear to be feasible.